Analisis Kinerja Keuangan Perusahaan Sebelum dan Sesudah Right Issue di BEI - Layuk Runtung, Guido Gian; Yadnya, I Putu (E-Jurnal Manajemen; Vol 7 No 3 (2018)DO - 10.24843/EJMUNUD.2018.v7.i03.p18, 2018)
The Purpose of this study was to analyze the diffrences in financial performance before and after right issue. Right issue a corporate action by the company by issuing new shares offered to existing shareholders. Sampling in this study using method purposive sampling. The samples in this research are 33 companies that conduct period 2011 – 2015. The financial performance in will be analysis through the five financial ratios namely CR, DER, TAT, ROA, and PER. This research data analysis technique using paired sample t test and Wilcoxon signed ranks test. The results showed that significant diffrences in TAT ratio before and after the right issue. While the research for the ratios of CR, DER, ROA, and PER showed no significant difference before and after right issue. These result indicate that the company’s financial performance two years after the right issue is more efficient in utilizing company’s assets in order to increase sales.